Supramolecular p/n‐heterojunction of C60‐functionalized bis(merocyanine) quadruple stack: A model system for charge carrier separation and recombination in organic solar cells. Issue 2 (10th March 2022) - Bialas, David; Fennel, Franziska; Noll, Niklas; Holzapfel, Marco; Schmiedel, Alexander; Lambert, Christoph; Würthner, Frank
Abstract: Supramolecular photosystems can afford important insights into elementary processes in molecular materials. Here, a bis(merocyanine)‐C60 conjugate composed of two covalently tethered electron‐donating merocyanine chromophores and two appended fullerene electron acceptor units is investigated. Concentration‐dependent UV/Vis studies in nonpolar solvents revealed a bimolecular association (dimerization) process, resulting in the formation of an H‐coupled merocyanine dye aggregate. The aggregate structure was confirmed by 2D NMR spectroscopy proving the presence of a well‐defined quadruple dye stack surrounded by four loosely connected fullerenes, which mimics the donor–acceptor interface in bulk heterojunction (BHJ) solar cells. Due to the interdigitation of the dyes in the quadruple stack motif, even at low concentrations, fully aggregated species prevail in nonpolar solvents, which enabled us to elucidate the photophysics of this supramolecular p/n‐heterojunction in dilute solution by femtosecond time‐resolved transient absorption spectroscopy. The observed photophysical processes include a favorably fast photoinduced electron transfer from the electron‐donating dye stack to the electron‐accepting fullerene moieties, a slower geminate charge carrier recombination of the generated electron and hole in the supramolecular p/n‐heterojunction as well as the formation of fullerene triplet states. While the geminate recombination of charge carriers is supposed to be less competitive in BHJ photovoltaic materials due to the possibility of fast electron migration within fullerene domains in thin films, intersystem crossing into the triplet manifold appears as a more critical undesired process. These insights from spectroscopy may help to tailor improved photovoltaic materials, thereby demonstrating the value of fundamental studies on elementary photophysical processes in molecular aggregates. KEY POINTS: Supramolecular p/n‐heterojunction by self‐assembly in solution Aggregate structure confirmed by NMR spectroscopy Photoinduced electron transfer studied by transient absorption spectroscopy Abstract : A well‐defined supramolecular p/n‐heterojunction has been realized through self‐assembly of a bis(merocyanine)‐C60 conjugate in nonpolar solvents. The structure of the quadruple dye stack could be verified by NMR spectroscopy and the photoinduced electron transfer from the dye stack to the fullerene units has been investigated by time‐resolved transient absorption spectroscopy. A fast charge separation followed by a slower charge recombination is observed as well as the formation of fullerene triplet states, which is an undesired process in organic solar cells.